The views of Ibn Kisan in the tools and grammatical vocabulary in the Book of the ErtshafAlthrab of Ibn Hayyan Andalusia (Journal of the College of Education for Women, 2019)
The scholars differed very much in determining the grammatical doctrine of Ibn Qaysan. It was said that he confused between the two sects and took the two groups(1) and that he took from Abu Abbas the fox and Abu al-Abbas almabrd(2).He was descended from the two sheikhs almbrad and fox(3), This research to find out his grammatical opinions in the tools and grammatical words that appeared in the Book of Resonance of Multiplication to the many reported by Ibn Hayyan in it, he has seen the books of Ibn Kisan did not reach us.The collection of these opinions and analysis is important for the scholars. Because the books of Ibn Kaysan specialized in grammar have lost their most important, the books that are similar to the book of Ibn al-Hayyan have remained a refuge for the knowledge of Ibn Qaysan's grammatical opinions. He may say that the views of Ibn Kaysan presented more than the study of (4) The right to study the tools and grammatical vocabulary in the Book of Resurrection of the beatings, because the views of the son of Kisan in which has not yet met, but selected the students some of them. As well as providing a great grammar vision such as Ibn Hayyan to the views of Ibn Kisan and his evaluation.